Direct charge carrier injection into Ga2O3 thin films using an In2O3 cathode buffer layer: their optical, electrical and surface state properties. (8th March 2017) - Cui, W; Zhao, X L; An, Y H; Guo, D Y; Qing, X Y; Wu, Z P; Li, P G; Li, L H; Cui, C; Tang, W H
Abstract: Conductive Ga2 O3 thin films with an In2 O3 buffer layer have been prepared on c -plane sapphire substrates using a laser molecular beam epitaxy technique. The effects of the In2 O3 buffer layer on the structure and optical, electrical and surface state properties of the Ga2 O3 films have been studied. The change in conductivity of the thin films is attributed to different thicknesses of the In2 O3 buffer layer, which determine the concentration of charge carriers injected into the upper Ga2 O3 layer from the interface of the bilayer thin films. In addition, the increase in flat band voltage shift and capacitance values as the In2 O3 buffer layer thickens are attributed to the increase in surface state density, which also contributes to the rapid shrinkage of the optical band gap of the Ga2 O3 . With transparency to visible light, high n -type conduction and the ability to tune the optical band gap and surface state density, we propose that Ga2 O3 /In2 O3 bilayer thin film is an ideal n -type semiconductor for fabrication of transparent power devices, solar cell electrodes and gas sensors.